Violación del principio de celeridad en las resoluciones administrativas y su influencia social y económica en los usuarios de la oficina técnica de Alausí del ministerio del ambiente, agua y transición ecológica durante el período enero a diciembre del 2020. - Condo Lovato, Sara Leonor (2022)
ABSTRACT: The purpose is to identify non-compliance with the principles of effectiveness, efficiency and quality of public administration in the technical office of the Alausí canton of the Ministry of the Environment, Water and Ecological Transition, by delaying the diligence and speed in Administrative Resolutions such as authorizations, renewals, cancellation / or reversion, substitution, approval of plans and approval of patterns of the use of water resources. Due to budgetary austerity, which prevents the appointing authority from hiring specialized public servants in the area, this investigative work will use the field methodology, since it will be carried out in the area where the problem arises, after identifying the problem that gave origin of the present investigation, a technical-legal report will be made, which will empower the appointing authority to make an inter- institutional cooperation agreement between Zonal Directorate 3 of the Ministry of Environment, Water and Ecological Transition and the Decentralized Autonomous Government of the Alausí canton, in order to strengthen strategic alliances between the parties that allow the appointment of legal professionals assigned to the Legal Advice area of the Technical Office of Alausí of the Ministry and in this way make up for the lack of human talent in the institution, guaranteeing its users due diligence and speed in their procedures. Keywords: Public Administration, efficiency, effectiveness, speed and Administrative Resolutions,